الأبعاد الفنية و التعليمية في السلسلة القصصية حكم و عبر لمحمد الصالح بن علي - سالم, عزوز, رانيا حسناء (Univesity of El-Oued, 2022)
تحاول هذه الدراسة " للأبعاد الفنية والتعليمية في السلسلة القصصية " حكم وعبر" لمحمد الصالح بن علي" تقصي واستنباط الأبعاد الفنية والتربوية والتعليمية من قصص الأطفال كموضوع مهم للأدب العربي. وتضمن البحث إشكالية أساسية وهي: ما مدى فاعلية البنية الفنيّة والجماليّة للقصة في تنمية مهارات الطفل وتربيته فكريًّا وأخلاقيًّا؟ ولتثمين هذه الدراسة اعتمدنا مناهج مختلفة: (البنيوي، النفسي، الاجتماعي) وما يتبعه من إجراءات الوصف والتحليل بهدف التمكن من الغوص في مضامين قصص هذه السلسلة وتفكيك بنياتها. وتمت دراسة الموضوع وفق خطة تتكون من مدخل وفصلين وخاتمة، كان الفصل الأول معنونًا بــ: الأبعاد الفنية للسلسلة القصصية " حكم وعبر" لــ محمد الصالح بن علي. أما الفصل الثاني موسوما بــ: الأبعاد التعليمية في السلسلة القصصية " حكم وعبر" لــ محمد الصالح بن علي. يعتبر محمد الصالح بن علي من أهم كُتاب القصة الموجهة للطفل في الجزائر، لذلك يجب التعريف به وتشجيع كتاباته لأنها ذات مضامين تربوية وأخلاقية وتعليمية بالإضافة إلى توفر الجانب الفني الجمالي فيها، فقد استطاع محمد الصالح بن علي التوفيق بين الجانب الفني الجمالي والتعليمي التربوي من أجل قصة متكاملة هدفها بناء طفل جزائري سويا نفسيًا واجتماعيًا وتربويًا. This study titled "The Artistic and Educational Dimensions in the Short Story Series 'Ahkam wa Ibar' by Muhammad Al-Saleh bin Ali" attempts to investigate and elicit the artistic and educational dimensions derived from children's stories as an important topic for Arabic literature. The research includes a basic problem: how effective is the artistic and aesthetic structure of the story in developing the child's skills and raising them intellectually and morally? In order to reinforce this study, we have adopted different approaches: (structural, psychological, and social). The procedures of description and analysis that follow in order to be able to delve into the contents of the stories of this series and dismantle their structures. The subject was studied according to a plan consisting of an introduction, two chapters, and a conclusion. The first chapter is titled "The Technical Dimensions of the Story Series “Hekam wa Ibar” by Muhammad Al-Saleh Bin Ali". As for the second chapter, it is titled "The Educational Dimensions in the Story Series “Hekam wa Ibar” by Muhammad Al-Saleh Bin Ali". Muhammad Al-Saleh bin Ali is considered one of the most important children-oriented story writers in Algeria, so he must be introduced, and his writings should be encouraged because they have an educational and moral content in addition to the availability of the artistic and aesthetic aspect in them. He could successfully integrate between the educational and aesthetic sides in order to make complete stories aimed at building an Algerian child psychologically, socially, and educationally.